The Influence of Human Resource Empowerment Management on Service Quality in the Department of Employment, Cooperatives and Small Medium Enterprises Sumedang Regency - Deden Ramdan (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Based on the observations of the researchers, it was shown that in the Field of Training, Placement and Expansion of Job Opportunities, the Department of Manpower, Cooperatives and Small and Medium Enterprises, Sumedang Regency, obtained information that there were problems regarding service quality (study of making job seeker cards). Researchers suspect that the problem is caused by the lack of empowerment of human resources, such as: lack of training, lack of complete work equipment and lack of motivation given by the leadership. The research method used is a descriptive analysis method with a quantitative approach. Data collection techniques were carried out in two ways, namely library research and field studies which included observations, interviews and questionnaires with analysis using a Likert scale. As for the determination of the sample used is using the saturated sampling technique. Furthermore, to test the instrument validity test using Pearson's product moment correlation and reliability test using Cronbach's alpha. Then to analyze the results using the correlation coefficient test to test the relationship, simple linear regression test to test the effect and the coefficient of determination test to determine the percentage of the influence of the human resource empowerment variable on service quality. The results of the study based on an analysis using the SPSS (Statistical & Product and Service Solution) version 21 program showed a strong level of influence between the empowerment of human resources on service quality with a value of 79.5% and the remaining 20.5% was influenced by the following factors.